2011
DOI: 10.1111/j.1742-6723.2011.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian artery laceration: A serious complication of needle decompression

Abstract: A 31-year-old woman presented with spontaneous tension pneumothorax. This was initially treated with needle decompression, which led to massive haemothorax. Treatment and methods to reduce the likelihood of this complication are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…29 Iatrogenic lesions of the internal mammary artery present a particular risk during needle decompression because of its anatomic proximity to the puncture site. 30 Therefore, it was the second aim of this work to provide population-based epidemiologic MRI data on the anatomic relationship between the internal mammary artery and the intended puncture track at the second ICS, MCL.…”
mentioning
confidence: 99%
“…29 Iatrogenic lesions of the internal mammary artery present a particular risk during needle decompression because of its anatomic proximity to the puncture site. 30 Therefore, it was the second aim of this work to provide population-based epidemiologic MRI data on the anatomic relationship between the internal mammary artery and the intended puncture track at the second ICS, MCL.…”
mentioning
confidence: 99%
“…Eightcentimeter needle RD based on CWT is greater than 96% at all sites, compared with the 5-cm needle RD rate of 66% to 81%, consistent with previously published 5-cm failure rates of 19% to 34%. 2,22,23 While there is no statistical difference in RD rates between 4AAL and 2MCL based on 8-cm needles, most practitioners have not started using 8-cm needles. Thus, the small but significantly thinner mean CWT at 4AAL compared with 2MCL and our corresponding RD data suggests improved rates of decompression at 4AAL for 5-cm needles as well.…”
Section: Discussionmentioning
confidence: 97%
“…A subsequent radiographic study in 2012 by the same author reported 16.7% failure of chest wall traversal at 5MAL compared with 42.5% failure at 2MCL based on a standard 5-cm needle. 23 Rawlins et al 17 in 2003 reported potential benefits in attempting NCD at the fifth ICS AAL. Nonetheless, 5-cm NCD at 2MCL is still the default.…”
Section: Discussionmentioning
confidence: 98%
“…[ 24 ] Rawlins et al .,[ 3 ] reported three cases of life-threatening hemorrhage after NT placement at the second intercostal space. In another example, Riwoe and Poncia[ 25 ] reported a thoracoscopically-documented injury of the left subclavian artery following NT misplacement into the first intercostal space.…”
Section: Anatomy and Techniquementioning
confidence: 99%